MENINGKATKAN PEMANFAATAN DAN PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN JASMANI MELALUI PENELITIAN TINDAKAN PARTISIPATORI - Suhadi, Suhadi (Jurnal Pendidikan Jasmani Indonesia, 2009)
This research was a clollaboration investigation among the Department of Physical Education-Yogyakarta State University, Learning Media Laboratory, and physical education teachers. The purpose of the research was to improve the use and the development of learning media in physical education teaching. This research was a partisipatory action research designed to solved problems about the use and the development of learning media in physical education class. Physical education teachers teaching in the neighborhood participated in this research. It employed three cycles which was decided by the paticipants themselves. In each cycle consists of such components as problem indentification, planning, acting, data collection, and reflection. Data were collected by observation and focus group discussion. Data analysis employed focused issues analysis. This result shows that teachers had a great appreciation on this research. Their understanding and ability in the development and the use of media have been improved. They also felt that the workshop really accomodated their needs on teaching as the research employed participatory approach. Kata kunci: media pembelajaran, guru pendidikan jasmani, penelitian tindakan partisipatori.